KAJIAN PERBANDINGAN LUAS WILAYAH DESA DAN KELURAHAN DI KECAMATAN MARGAHAYU, KABUPATEN BANDUNG - Baskoro Tri Julianto; Yuli Suharnoto (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2024)
Bandung Regency is one of the regencies in West Java Province which consists of 31 sub-districts. One of the important sub-districts in Bandung Regency is Margahayu sub-district. This sub-district is one of the buffer areas between the city of Bandung and Bandung Regency. Margahayu sub-district consists of four Desa and one kelurahan, each of which has a different area based on statistical data published by BPS Bandung Regency from 2021 to 2023. This study aims to show how big the difference in area is compared to the area calculated with the help of Arcmap 10.8 software. The results of the analysis show that the area data released in 2021 and 2023 based on data in 2020 and 2022 is considered quite good with the value of the sum of squared residuals of both being 4,14.